Dental and Oral Health Maintenance Behavior in Students of SMAN 5 Palembang in The Covid-19 Pandemic - Eka Melinia Kusuma Wardani; Martha Mozartha; Helios Sutiyoso (Sriwijaya Journal of Dentistry, 2021)
Introduction: Caries and periodontitis are the most common dental and oral health problems in Indonesia. Tooth brushing is one way to prevent caries and maintain dental and oral health. In addition, education and knowledge level are the influencing factors. During the COVID-19 pandemic, the dental practice was mostly closed and only accepted emergency patients, access to dental practice was limited. Purpose: To describe the behavior of dental and oral health maintenance in class XI students of SMAN 5 Palembang during the COVID-19 pandemic. Methods:  The descriptive survey research used an online questionnaire using Google form containing 21 questions. Subjects involved in this study were 70 students in class XI SMAN 5 Palembang.  Results: Most students brush their teeth at the right time, duration and method. Visits to the dentist are still relatively low. Only 50% of students had been to the dentist before the COVID-19 pandemic, and only 14% had been to the dentist during the pandemic. Students who attended webinars on social media during the COVID-19 pandemic were only 16%. Conclusion:  Students' behavior in maintaining dental and oral health is quite acceptable, but health promotion is needed.